Neurogenesis, Neurodegeneration, Interneuron Vulnerability, and Amyloid-β in the Olfactory Bulb of APP/PS1 Mouse Model of Alzheimer's Disease - De la Rosa-Prieto, Carlos; Saiz-Sanchez, Daniel; Ubeda-Banon, Isabel; Flores-Cuadrado, Alicia; Martinez-Marcos, Alino (Frontiers in Neuroscience, 2016)
Alzheimer´s disease is the most prevalent neurodegenerative disease, mostly idiopathic and with palliative treatment. Neuropathologically, it is characterized by intracellular neurofibrillary tangles of tau protein and extracellular plaques of amyloid β peptides. The relationship between Alzheimer’s disease and neurogenesis is unknown, but two facts are particularly relevant. First, early aggregation sites of both proteinopathies include the hippocampal formation and the olfactory bulb, which have been correlated to memory and olfactory deficits, respectively. These areas are well-recognized integration zones of newly-born neurons in the adult brain. Second, molecules, such as amyloid precursor protein and presenilin-1 are common to both Alzheimer’s disease etiology and neurogenic development. Adult neurogenesis in Alzheimer’s disease models has been studied in the hippocampus, but only occasionally addressed in the olfactory bulb and results are contradictory. To gain insight on the relationship between adult neurogenesis and Alzheimer’s disease, this work analyzes neurogenesis, neurodegeneration, interneuron vulnerability and amyloid-β involvement in the olfactory bulb of an Alzheimer’s disease model. Control and double-transgenic mice carrying the amyloid precursor protein and the presenilin-1 genes, which give rise amyloid β plaques have been used. BrdU-treated animals have been studied at 16, 30, 43 and 56 weeks of age. New-born cell survival (BrdU), neuronal loss (using neuronal markers NeuN and PGP9.5), differential interneuron (calbindin-, parvalbumin-, calretinin- and somatostatin-expressing populations) vulnerability and involvement by amyloid β have been analyzed. Neurogenesis increases with aging in the granule cell layer of control animals from 16 to 43 weeks. No neuronal loss has been observed after quantifying NeuN or PGP9.5. Regarding interneuron population vulnerability: calbindin-expressing neurons remains unchanged; parvalbumin-expressing neurons trend to increase with aging in transgenic animals; calretinin-expressing neurons increase with aging in transgenic mice and decrease in control animals and neurogenesis is higher in control as compared to transgenic animals at given ages, finally; somatostatin-expressing neurons of transgenic mice decrease with aging and as compared to controls. Amyloid β aggregates with aging in the granule cell layer, which may be related to the particular involvement of somatostatin-expressing cells.